Perovskite solar cell
By using malonimide hydrochloride as an interface modifier in perovskite solar cells, the crystallization behavior of perovskite films is regulated, and the problems of poor photoelectric conversion efficiency and poor stability of perovskite solar cells are solved, and higher photoelectric conversion efficiency and stability are achieved.
Patent Information
- Application Number
- CN202411994378.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
The existing perovskite solar cells have a large number of defects, resulting in poor photoelectric conversion efficiency, and the defects are instable under external stimulation, which seriously accelerates the degradation of the perovskite layer.
Malonimide hydrochloride is used as an interface modifier to prepare an interface modification layer on the surface of the perovskite active layer, or directly add it to the perovskite precursor solution to regulate the crystallization behavior of the perovskite film, form low-dimensional perovskites, and improve interface energy band arrangement and carrier transfer.
It effectively improves the stability and photoelectric conversion efficiency of perovskite solar cells, reduces the non-radiative recombination of interface carriers, and extends the service life of the device.
Smart Images

Figure BDA0005224282630000041
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite solar cells, and in particular to a perovskite solar cell. Background Art
[0002] With the continuous development of society, people's demand for energy is also increasing. However, fossil energy is on the verge of exhaustion, and the use of fossil energy is accompanied by environmental problems. In order to deal with these energy problems, clean and pollution-free renewable energy must be developed. Among technologies such as solar energy, geothermal energy, wind energy, ocean energy, and biomass energy, solar energy has become the most promising clean energy because of its large reserves and convenient access. At present, solar cells are the most common way to utilize solar energy. Among various solar cells, perovskite solar cells have attracted widespread attention due to their low cost, simple process, and high photoelectric conversion efficiency.
[0003] However, the perovskite solar cells prepared by the solution method currently have a large number of defects. These defects are unstable under external stimuli (light, heat, moisture, oxygen). Some halide defects promote ion migration in the perovskite, which seriously accelerates the degradation of the perovskite layer. These defects will form a large number of carrier recombination centers, which ultimately lead to a decrease in device performance. In order to reduce the generation of defects, people often use some interface modifiers. The improvement of the interface can not only improve the interface charge transfer but also assist in the formation of high-quality perovskite films, reduce the defects of perovskite solar cells, and thus achieve the purpose of improving device performance. Summary of the invention
[0004] The main purpose of the present invention is to provide a perovskite solar cell to solve the technical problem of poor photoelectric conversion efficiency of perovskite solar cells.
[0005] To achieve the above object, the present invention provides a perovskite solar cell, wherein the preparation method of the perovskite solar cell comprises method one, method two or method three.
[0006] The method 1 comprises the following steps:
[0007] dissolving malonyl amidine hydrochloride in a solvent to obtain a malonyl amidine hydrochloride solution, coating the malonyl amidine hydrochloride solution on the surface of the hole transport layer to form an interface modification layer, and then preparing a perovskite active layer on the surface of the interface modification layer;
[0008] The second method comprises the following steps:
[0009] Adding malonyl amidine hydrochloride to a perovskite precursor solution, and coating the perovskite precursor solution with the malonyl amidine hydrochloride added to the surface of the hole transport layer to prepare a perovskite active layer;
[0010] The method three comprises the following steps:
[0011] Malonyl amidine hydrochloride is dissolved in a solvent to obtain a malonyl amidine hydrochloride solution, the malonyl amidine hydrochloride solution is coated on the surface of the perovskite active layer to form an interface modification layer, and then a hole transport layer is prepared on the surface of the interface modification layer.
[0012] In some embodiments of the present invention, in the method 1, the mass concentration of malonylamidine hydrochloride in the malonylamidine hydrochloride solution is 0.1 mg / mL to 3 mg / mL;
[0013] And / or, the solvent includes at least one of isopropanol and ethanol.
[0014] In some embodiments of the present invention, in the method 1, the interface modification layer is prepared by spin coating;
[0015] And / or, after the malonyl amidine hydrochloride solution is coated on the surface of the hole transport layer, an annealing treatment is further performed.
[0016] In some embodiments of the present invention, the interface modification layer is prepared by spin coating, and the spin coating rotation speed is 3000 rpm to 4000 rpm; and / or the spin coating time is 30s to 35s.
[0017] In some embodiments of the present invention, after the malonyl amidine hydrochloride solution is coated on the surface of the hole transport layer, an annealing treatment is further performed, and the annealing temperature is 100° C. to 150° C.; and / or the annealing time is 10 min to 30 min.
[0018] In some embodiments of the present invention, in the second method, the mass concentration of malonyl amidine hydrochloride in the perovskite precursor solution is 0.1 mg / mL to 3 mg / mL.
[0019] In some embodiments of the present invention, in the method three, the mass concentration of malonyl amidine hydrochloride in the malonyl amidine hydrochloride solution is 0.1 mg / mL to 3 mg / mL; and / or the solvent includes at least one of isopropanol and ethanol.
[0020] In some embodiments of the present invention, in the method one, the perovskite solar cell comprises, from bottom to top, a transparent conductive oxide layer, a hole transport layer, an interface modification layer, a perovskite active layer, an electron transport layer, a hole blocking layer and a back electrode.
[0021] In some embodiments of the present invention, in the second method, the perovskite solar cell includes, from bottom to top, a transparent conductive oxide layer, a hole transport layer, a perovskite active layer, an electron transport layer, a hole blocking layer and a back electrode.
[0022] In some embodiments of the present invention, in the method three, the perovskite solar cell includes, from bottom to top, a transparent conductive oxide layer, an electron transport layer, the perovskite active layer, the interface modification layer, the hole transport layer and a back electrode.
[0023] The beneficial effects that can be achieved by the present invention are:
[0024] The invention uses malonyl amidine hydrochloride as an interface modifier to prepare an interface modification layer on the surface of a perovskite active layer, or directly adds the malonyl amidine hydrochloride as an additive to a perovskite precursor solution to prepare a perovskite active layer doped with malonyl amidine hydrochloride. The formamidine group and lead halide in the malonyl amidine hydrochloride can form a low-dimensional perovskite, which can effectively improve the interface energy band arrangement, promote the transfer and extraction of interface carriers, and inhibit the non-radiative recombination of interface carriers. Meanwhile, the malonyl amidine hydrochloride contains an amide group, and the carbonyl group in the amide group can chelate with lead to play a role in regulating the crystallization of the perovskite active layer, thereby achieving the purpose of improving the stability and photoelectric conversion efficiency of the perovskite solar cell.
[0025] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments. DETAILED DESCRIPTION
[0026] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0029] The present invention provides a perovskite solar cell. The preparation method of the perovskite solar cell includes method one, method two or method three.
[0030] Method 1 comprises the following steps: dissolving malonyl amidine hydrochloride in a solvent to obtain a malonyl amidine hydrochloride solution, coating the malonyl amidine hydrochloride solution on the surface of a hole transport layer to form an interface modification layer, and then preparing a perovskite active layer on the surface of the interface modification layer.
[0031] Method 2 includes the following steps: adding malonyl amidine hydrochloride to a perovskite precursor solution, and coating the perovskite precursor solution with malonyl amidine hydrochloride added to the surface of a hole transport layer to prepare a perovskite active layer.
[0032] Method three includes the following steps: dissolving malonyl amidine hydrochloride in a solvent to obtain a malonyl amidine hydrochloride solution, coating the malonyl amidine hydrochloride solution on the surface of the perovskite active layer to form an interface modification layer, and then preparing a hole transport layer on the surface of the interface modification layer.
[0033] In the present invention, the perovskite solar cell prepared by method one includes a hole transport layer, an interface modification layer containing malonyl amidine hydrochloride, and a perovskite active layer stacked in sequence, and is an inverted perovskite solar cell; the perovskite solar cell prepared by method two includes a hole transport layer and a perovskite active layer doped with malonyl amidine hydrochloride stacked in sequence, and is an inverted perovskite solar cell; the perovskite solar cell prepared by method three includes a perovskite active layer, an interface modification layer containing malonyl amidine hydrochloride, and a hole transport layer stacked in sequence, and is an upright perovskite solar cell.
[0034] The present invention uses malonyl amidine hydrochloride as an interface modifier to prepare an interface modification layer on the surface of a perovskite active layer, or directly adds it as an additive to a perovskite precursor solution to prepare a perovskite active layer doped with malonyl amidine hydrochloride. The crystallization behavior of the perovskite film can be regulated to prepare a uniform, dense, high-crystallinity, and vertically oriented perovskite film. Moreover, low-latitude perovskite can be formed at the buried interface to reduce energy level barriers, thereby achieving the purpose of improving the stability and photoelectric conversion efficiency of the perovskite solar cell.
[0035] The structural formula of malonyl amidine hydrochloride is as follows:
[0036]
[0037] From the structural formula, we can know that malonyl amidine hydrochloride contains formamidine groups, which can form low-latitude perovskites with lead halides in perovskite materials, effectively improving the interface energy band arrangement, promoting interface carrier transfer and extraction, and inhibiting the non-radiative recombination of interface carriers. Malonyl amidine hydrochloride also contains amide groups. The carbonyl group in the amide group can chelate with lead and play a role in regulating the crystallization of the perovskite active layer. In addition, malonyl amidine hydrochloride, as an interface modifier, can reduce the direct contact between perovskite and adjacent functional layers such as nickel oxide in the hole transport layer caused by incomplete coverage of self-assembled single molecules, thereby blocking the adverse reaction between high-valent nickel ions and perovskite and effectively passivating buried interface defects.
[0038] In some embodiments of method one, the mass concentration of malonylamidine hydrochloride in the malonylamidine hydrochloride solution is 0.1 mg / mL to 3 mg / mL, and can be any value in the range of 0.1 mg / mL to 3 mg / mL, such as 0.1 mg / mL, 0.5 mg / mL, 0.8 mg / mL, 1 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, etc.
[0039] In some embodiments of method 1, the solvent for dissolving malonyl amidine hydrochloride includes at least one of isopropanol and ethanol.
[0040] In some embodiments of method 1, the interface modification layer can be prepared by spin coating. For example, the malonyl amidine hydrochloride solution can be coated on the surface of the hole transport layer by spin coating to form the interface modification layer.
[0041] In some embodiments of method 1, the interface modification layer is prepared by spin coating, the spin coating speed is 3000 rpm to 4000 rpm, and the spin coating time is 30s to 35s.
[0042] In some embodiments of method 1, after the malonyl amidine hydrochloride solution is coated on the surface of the hole transport layer, an annealing treatment is further performed.
[0043] In some embodiments, after the malonyl amidine hydrochloride solution is coated on the surface of the hole transport layer, an annealing treatment is further performed, the annealing temperature is 100° C. to 150° C., and the annealing time is 10 min to 30 min.
[0044] In some embodiments of method one, the preparation of functional layers such as an electron transport layer, a hole blocking layer, and a back electrode is also included.
[0045] In one embodiment, method 1 comprises the following steps:
[0046] preparing a transparent conductive oxide layer;
[0047] preparing a hole transport layer on the surface of the transparent conductive oxide layer;
[0048] The interface modification layer of method 1 is prepared on the surface of the hole transport layer;
[0049] preparing a perovskite active layer on the surface of the interface modification layer;
[0050] preparing an electron transport layer on the surface of the perovskite active layer;
[0051] preparing a hole blocking layer on the surface of the electron transport layer;
[0052] A back electrode is prepared on the surface of the electron transport layer.
[0053] The perovskite solar cell prepared by the above method 1 is an inverted perovskite cell, which includes a transparent conductive oxide layer, a hole transport layer, an interface modification layer, a perovskite active layer, an electron transport layer, a hole blocking layer and a back electrode from bottom to top.
[0054] In this embodiment, the present invention uses malonyl amidine hydrochloride as an interface modifier to prepare an interface modification layer on the lower surface of the perovskite active layer, which can regulate the crystallization behavior of the perovskite film, prepare a uniform, dense, high-crystallinity, and vertically oriented perovskite film, and can form low-latitude perovskites at the buried interface to reduce energy level barriers, thereby achieving the purpose of improving the stability and photoelectric conversion efficiency of perovskite solar cells. When the hole transport layer contains nickel oxide, malonyl amidine hydrochloride can also reduce the direct contact between perovskite and nickel oxide caused by incomplete coverage of self-assembled single molecules, thereby blocking the adverse reaction between high-valent nickel ions and perovskite, effectively passivating buried interface defects, and thus improving the stability and photoelectric conversion efficiency of battery devices.
[0055] In some embodiments of method 2, the mass concentration of malonyl amidine hydrochloride in the perovskite precursor solution is 0.1 mg / mL to 3 mg / mL, and can be any value in the range of 0.1 mg / mL to 3 mg / mL, such as 0.1 mg / mL, 0.5 mg / mL, 0.8 mg / mL, 1 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, etc.
[0056] In some embodiments of the second method, the preparation of functional layers such as an electron transport layer, a hole blocking layer, and a back electrode is also included.
[0057] In one embodiment, method 2 includes the following steps:
[0058] preparing a transparent conductive oxide layer;
[0059] preparing a hole transport layer on the surface of the transparent conductive oxide layer;
[0060] The perovskite active layer in the second method is prepared on the surface of the hole transport layer;
[0061] preparing an electron transport layer on the surface of the perovskite active layer;
[0062] preparing a hole blocking layer on the surface of the electron transport layer;
[0063] A back electrode is prepared on the surface of the hole blocking layer.
[0064] The perovskite solar cell prepared by the above method 2 is an inverted perovskite solar cell, which includes a transparent conductive oxide layer, a hole transport layer, a perovskite active layer, an electron transport layer, a hole blocking layer and a back electrode from bottom to top.
[0065] In this embodiment, the present invention uses malonyl amidine hydrochloride as an additive added to the perovskite precursor solution to prepare the perovskite active layer, which can regulate the crystallization behavior of the perovskite film, prepare a uniform, dense, high-crystallinity and vertically oriented perovskite film, and can form low-latitude perovskite at the buried interface to reduce energy level barriers, thereby achieving the purpose of improving the stability and photoelectric conversion efficiency of the perovskite solar cell. When the hole transport layer contains nickel oxide, malonyl amidine hydrochloride can also reduce the direct contact between the perovskite and the nickel oxide caused by incomplete coverage of the self-assembled single molecule, thereby blocking the adverse reaction between the high-valent nickel ions and the perovskite, effectively passivating the buried interface defects, and thus improving the stability and photoelectric conversion efficiency of the battery device.
[0066] In some embodiments of method three, the mass concentration of malonyl amidine hydrochloride in the malonyl amidine hydrochloride solution is 0.1 mg / mL to 3 mg / mL, and can be any value in the range of 0.1 mg / mL to 3 mg / mL, such as 0.1 mg / mL, 0.5 mg / mL, 0.8 mg / mL, 1 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, etc.
[0067] In some embodiments of method three, the solvent for dissolving malonyl amidine hydrochloride includes at least one of isopropanol and ethanol.
[0068] In some embodiments of method three, the interface modification layer can be prepared by spin coating. For example, the interface modification layer can be formed by coating the malonyl amidine hydrochloride solution onto the surface of the hole transport layer by spin coating.
[0069] In some embodiments of method three, the interface modification layer is prepared by spin coating, the spin coating speed is 3000 rpm to 4000 rpm, and the spin coating time is 30s to 35s.
[0070] In some embodiments of method three, after the malonyl amidine hydrochloride solution is coated on the surface of the perovskite active layer, an annealing treatment is further performed.
[0071] In some embodiments, after the malonyl amidine hydrochloride solution is coated on the surface of the perovskite active layer, an annealing treatment is further performed, the annealing temperature is 100° C. to 150° C., and the annealing time is 10 min to 30 min.
[0072] In some embodiments of method three, the preparation of functional layers such as an electron transport layer and a back electrode is also included.
[0073] In one embodiment, method three includes the following steps:
[0074] preparing a transparent conductive oxide layer;
[0075] preparing an electron transport layer on the surface of the transparent conductive oxide layer;
[0076] preparing a perovskite active layer on the surface of the electron transport layer;
[0077] The interface modification layer of method 3 is prepared on the surface of the perovskite active layer;
[0078] preparing a hole transport layer on the surface of the interface modification layer;
[0079] A back electrode is prepared on the surface of the hole transport layer.
[0080] The perovskite solar cell prepared by the above method three is an upright perovskite solar cell, which includes a transparent conductive oxide layer, an electron transport layer, a perovskite active layer, an interface modification layer, a hole transport layer and a back electrode from bottom to top.
[0081] The present embodiment sets an interface modification layer on the upper surface of the perovskite active layer, and the malonyl amidine hydrochloride in the interface modification layer acts as a passivator, can be covered on the surface of the perovskite film, interacts with defect sites, thereby passivating these defects, reducing charge recombination, and improving the performance of the device. Secondly, malonyl amidine hydrochloride can also optimize the interface energy level structure of the perovskite solar cell, and by adjusting the chemical composition and thickness of the passivation layer, the energy level matching degree between the perovskite film and the electron transport layer or the hole transport layer can be regulated, which helps to achieve efficient separation and transmission of photogenerated carriers at the interface, and further improves the photoelectric conversion efficiency of the device. In addition, during long-term use, the perovskite film may be affected by external factors such as light, heat, and humidity and degraded or aged, and the interface modification layer prepared by malonyl amidine hydrochloride as a passivation layer can enhance the stability and durability of the perovskite solar cell, can protect the perovskite film from the above-mentioned adverse factors, and extend the service life of the device.
[0082] In the present invention, the transparent conductive oxide layer in method 1 to method 3 is prepared by transparent conductive oxide, and the transparent conductive oxide includes indium tin oxide (ITO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO) and the like.
[0083] In the present invention, the inverted perovskite solar cell prepared by method 1 and method 2 is prepared, and the material for preparing the electron transport layer includes an electron transport material suitable for the inverted perovskite solar cell, such as C 60 , fullerene derivatives (PCBM). The method three produces an upright perovskite solar cell, and the material for preparing the electron transport layer includes an electron transport material suitable for the upright perovskite solar cell, such as at least one of SnO2 and TiO2.
[0084] In the present invention, the material for preparing the perovskite active layer in methods 1 to 3 includes a perovskite material, and the structural formula of the perovskite material is ABX3, wherein A includes an organic cation or an inorganic cation, for example, MA + , FA + , Cs + At least one of the above, the B position includes a metal cation, such as Pb 2+ Sn 2+ At least one of the following, the X position includes a halogen anion, for example, Br - ,I - , Cl - At least one of .
[0085] In the present invention, the material of the hole blocking layer prepared in method 1 or method 2 includes bathocuproine (BCP) and the like.
[0086] In the present invention, the material of the back electrode prepared in method 1 to method 3 includes metal materials, such as Ag, Cu, Au, etc.
[0087] In the present invention, the inverted perovskite solar cells prepared by method one and method two, the materials of the hole transport layer include hole transport materials suitable for inverted perovskite solar cells, including nickel oxide, etc. The nickel oxide solution obtained by dissolving the nickel oxide can be spin-coated onto the surface of the substrate to obtain the hole transport layer.
[0088] In the present invention, method three prepares an upright perovskite solar cell, and the material of the hole transport layer includes hole transport materials suitable for upright perovskite solar cells, including 2,2′,7,7′-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (Spiro-OMeTAD) and the like.
[0089] In method one and method two, the hole transport layer is prepared from a hole transport material, and the hole transport material includes nickel oxide. In the present embodiment, the hole transport layer contains high-valent nickel ions, which are prone to adverse reactions with the perovskite material in the perovskite active layer, affecting the stability and photoelectric conversion efficiency of the battery, and the present invention can prepare the interface modification layer of the present invention on the surface of the hole transport layer, or directly add malonyl amidine hydrochloride to the perovskite active layer, and the malonyl amidine hydrochloride in the interface modification layer and the malonyl amidine hydrochloride in the perovskite active layer can reduce the direct contact between the perovskite and the nickel oxide caused by the incomplete coverage of the self-assembled monomolecule, thereby blocking the adverse reaction between the high-valent nickel ions and the perovskite, effectively passivating the buried interface defects, thereby improving the stability and photoelectric conversion efficiency of the battery device.
[0090] In method three, the perovskite solar cell includes a transparent conductive oxide layer, a hole transport layer, a perovskite active layer, an interface modification layer of the present invention, an electron transport layer and a back electrode from bottom to top. In this embodiment, an interface modification layer is arranged on the upper surface of the perovskite active layer. The malonyl amidine hydrochloride in the interface modification layer acts as a passivating agent, which can cover the surface of the perovskite film and interact with defect sites, thereby passivating these defects, reducing charge recombination, and improving the performance of the device. Secondly, malonyl amidine hydrochloride can also optimize the interface energy level structure of the perovskite solar cell. By adjusting the chemical composition and thickness of the passivation layer, the energy level matching degree between the perovskite film and the electron transport layer or the hole transport layer can be regulated, which helps to achieve efficient separation and transmission of photogenerated carriers at the interface, and further improves the photoelectric conversion efficiency of the device. In addition, during long-term use, the perovskite film may be affected by external factors such as light, heat, and humidity and degrade or age. The interface modification layer prepared by malonylamine hydrochloride as a passivation layer can enhance the stability and durability of perovskite solar cells, protect the perovskite film from the above-mentioned adverse factors, and extend the service life of the device.
[0091] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0092] Example 1
[0093] Example 1 Preparation of perovskite solar cells using method 1:
[0094] Preparation of transparent conductive oxide layer
[0095] The TCO conductive glass was ultrasonically cleaned for 15 min using glass cleaning agent, deionized water, isopropyl alcohol and acetone in sequence, and then the TCO conductive glass was blown dry with a nitrogen flow and then subjected to ultraviolet ozone cleaning (UVO) treatment for 15 min.
[0096] Preparation of hole transport layer
[0097] A nickel oxide aqueous solution with a concentration of 10 mg / mL was deposited on the surface of the TCO conductive glass by spin coating, the spin coating speed was 3000 rpm, the spin coating time was 30 s, and the nickel oxide layer was obtained on the surface of the TCO conductive substrate by annealing at 150°C for 10 min; then a N-cyclohexyl-2-benzothiazolesulfonamide (CZ-CPA) solution with a concentration of 0.3 mg / mL was deposited on the surface of the nickel oxide layer of the TCO conductive glass by spin coating, the spin coating speed was 3000 rpm, the spin coating time was 30 s, and the hole transport layer was obtained by annealing at 100°C for 10 min.
[0098] Preparation of interface modification layer
[0099] Malonyl amidine hydrochloride was dissolved in ethanol solution to obtain a 0.9 mg / mL malonyl amidine hydrochloride solution, which was deposited on the surface of the hole transport layer by spin coating at a speed of 3000 rpm for 30 s. The interface modification layer was annealed at 100° C. for 5 min.
[0100] Preparation of perovskite active layer
[0101] 18.2 mg of CsI, 194.5 mg of FAI, 31.7 mg of MAI, 500.2 mg of PbI2 and 115.6 mg of PbBr2 were dissolved in 1 mL of a mixed solution of DMF and DMSO with a volume ratio of 8:2, and then heated and stirred at 60 ° C for 1 hour to obtain a perovskite precursor solution. The sample with the prepared hole transport layer was spin-coated with 100 μL of the prepared perovskite precursor solution at a low speed of 1000 rpm and a high speed of 4000 rpm in a nitrogen glove box, respectively. The spin coating time was 10 s and 35 s, respectively. When the total time was 10 s, the anti-solvent chlorobenzene was added dropwise, and then annealed at 100 ° C for 30 minutes to obtain a perovskite active layer.
[0102] Preparation of electron transport layer
[0103] The electron transport layer C with a thickness of 30 nm was prepared by vacuum thermal evaporation. 60 .
[0104] Preparation of hole blocking layer
[0105] A bathocuproin (BCP) hole blocking layer with a thickness of 7 nm was prepared by vacuum thermal evaporation.
[0106] Preparation of back electrode
[0107] The Cu back electrode with a thickness of 100 nm was prepared by vacuum thermal evaporation.
[0108] Example 2
[0109] The preparation method of Example 2 is substantially the same as that of Example 1, except that the concentration of malonyl amidine hydrochloride is 0.1 mg / mL.
[0110] Example 3
[0111] The preparation method of Example 3 is substantially the same as that of Example 1, except that the concentration of malonyl amidine hydrochloride is 0.3 mg / mL.
[0112] Example 4
[0113] The preparation method of Example 4 is substantially the same as that of Example 1, except that the concentration of malonyl amidine hydrochloride is 0.6 mg / mL.
[0114] Example 5
[0115] The preparation method of Example 5 is substantially the same as that of Example 1, except that the concentration of malonyl amidine hydrochloride is 1.2 mg / mL.
[0116] Example 6
[0117] Example 6 Preparation of perovskite solar cells using method 2:
[0118] Preparation of transparent conductive oxide layer
[0119] The TCO conductive glass was ultrasonically cleaned for 15 min using glass cleaning agent, deionized water, isopropyl alcohol and acetone in sequence, and then the TCO conductive glass was blown dry with a nitrogen flow and then subjected to ultraviolet ozone cleaning (UVO) treatment for 15 min.
[0120] Preparation of hole transport layer
[0121] A nickel oxide aqueous solution with a concentration of 10 mg / mL was deposited on the surface of the TCO conductive glass by spin coating, the spin coating speed was 3000 rpm, the spin coating time was 30 s, and the nickel oxide layer was obtained on the surface of the TCO conductive substrate by annealing at 150°C for 10 min; then a N-cyclohexyl-2-benzothiazolesulfonamide (CZ-CPA) solution with a concentration of 0.3 mg / mL was deposited on the surface of the nickel oxide layer of the TCO conductive substrate by spin coating, the spin coating speed was 3000 rpm, the spin coating time was 30 s, and the hole transport layer was obtained by annealing at 100°C for 10 min.
[0122] Preparation of perovskite active layer
[0123] 18.2 mg of CsI, 194.5 mg of FAI, 31.7 mg of MAI, 500.2 mg of PbI2 and 115.6 mg of PbBr2 were dissolved in 1 mL of a mixed solution of DMF and DMSO in a volume ratio of 8:2, and then heated and stirred at 60°C for 1 h to obtain a perovskite precursor solution, and malonyl amidine hydrochloride was added to the perovskite precursor solution at an addition amount of 0.3 mg / mL. The sample with the prepared hole transport layer was spin-coated with 100 μL of the perovskite precursor solution containing malonyl amidine hydrochloride at a low speed of 1000 rpm and a high speed of 4000 rpm in a nitrogen glove box, respectively. The spin coating time was 10 s and 35 s, respectively. When the total time was 10 s, the anti-solvent chlorobenzene was added dropwise, followed by annealing at 100°C for 30 minutes to obtain a perovskite active layer.
[0124] Preparation of electron transport layer
[0125] The electron transport layer C with a thickness of 30 nm was prepared by vacuum thermal evaporation. 60 .
[0126] Preparation of hole blocking layer
[0127] A bathocuproin (BCP) hole blocking layer with a thickness of 7 nm was prepared by vacuum thermal evaporation.
[0128] Preparation of back electrode
[0129] A Cu back electrode with a thickness of 100 nm was prepared on the surface of the hole blocking layer by vacuum thermal evaporation.
[0130] Example 7
[0131] Example 7 Preparation of perovskite battery using method 3:
[0132] Preparation of transparent conductive oxide layer
[0133] The TCO conductive glass was ultrasonically cleaned for 15 min using glass cleaning agent, deionized water, isopropyl alcohol and acetone in sequence, and then the TCO conductive glass was blown dry with a nitrogen flow and then subjected to ultraviolet ozone cleaning (UVO) treatment for 15 min.
[0134] Preparation of electron transport layer
[0135] 0.5 mL of 15% SnO2 aqueous solution was added into 2.5 mL of deionized water, and the electron transport layer precursor solution was obtained after ultrasonic vibration for 20 min. 150 uL of the electron transport layer precursor solution was spin coated onto the surface of the transparent conductive glass at a spin coating speed of 3000 rpm, a spin coating time of 15 s, and a spin coating acceleration of 2000 rpm / s. The electron transport layer was then annealed on a hot plate at 150°C for 45 min.
[0136] Preparation of perovskite active layer
[0137] 18.2 mg of CsI, 194.5 mg of FAI, 31.7 mg of MAI, 500.2 mg of PbI2 and 115.6 mg of PbBr2 were dissolved in 1 mL of a mixed solution of DMF and DMSO with a volume ratio of 8:2, and then heated and stirred at 60 ° C for 1 hour to obtain a perovskite precursor solution. The sample with the prepared hole transport layer was spin-coated with 100 μL of the prepared perovskite precursor solution at a low speed of 1000 rpm and a high speed of 4000 rpm in a nitrogen glove box, respectively. The spin coating time was 10 s and 35 s, respectively. When the total time was 10 s, the anti-solvent chlorobenzene was added dropwise, and then annealed at 100 ° C for 30 minutes to obtain a perovskite active layer.
[0138] Preparation of interface modification layer
[0139] Malonyl amidine hydrochloride was dissolved in an ethanol solution to obtain a 0.9 mg / mL malonyl amidine hydrochloride solution, which was deposited on the surface of the perovskite active layer by spin coating at a speed of 3000 rpm for 30 s. The interface modification layer was annealed at 100° C. for 5 min.
[0140] Preparation of hole transport layer
[0141] 140 mg of Spiro-OMeTAD was dissolved in 2 mL of chlorobenzene, and then 30 μl of 520 mg / mL lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) acetonitrile solution was added to obtain a hole transport layer precursor solution. 100 μl of the hole transport layer precursor solution was spin coated on the surface of the interface modification layer at a spin coating speed of 4000 rpm, a spin coating time of 30 s, and a spin coating acceleration of 2000 rpm / s to obtain a hole transport layer.
[0142] Preparation of back electrode
[0143] A Cu back electrode with a thickness of 100 nm was prepared on the surface of the hole transport layer by vacuum thermal evaporation.
[0144] Comparative Example 1
[0145] The preparation method of Comparative Example 1 is substantially the same as that of Example 1, except that no interface modification layer is prepared.
[0146] Table 1 Performance comparison of the products obtained from Examples 1 to 7 and Comparative Example 1
[0147] Test items <![CDATA[Short-circuit current (mAcm -2 )]]> Open circuit voltage(V) Photoelectric conversion efficiency (%) Fill factor (%) Example 1 24.84 1.13 23.39 83.34 Example 2 23.67 1.11 21.35 81.27 Example 3 24.43 1.11 22.18 81.78 Example 4 24.69 1.12 22.67 81.98 Example 5 24.52 1.12 22.29 81.16 Example 6 24.53 1.12 22.54 82.06 Example 7 24.25 1.11 22.16 82.34 Comparative Example 1 23.24 1.10 20.33 79.54
[0148] In Examples 1 to 7, malonyl amidine hydrochloride is used as an interface modifier to prepare an interface modification layer between the perovskite active layer and the hole transport layer, or is directly added as an additive to the perovskite precursor solution to prepare a perovskite active layer doped with malonyl amidine hydrochloride. Malonyl amidine hydrochloride contains a formamidine group, which can form a low-latitude perovskite with the lead halide in the perovskite material, which can effectively improve the interface energy band arrangement, promote interface carrier transfer and extraction, and inhibit the non-radiative recombination of interface carriers; malonyl amidine hydrochloride also contains an amide group, and the carbonyl group in the amide group can chelate with lead, thereby regulating the crystallization of the perovskite active layer, thereby achieving the purpose of improving the photoelectric conversion efficiency and stability of the battery device. In addition, the hole transport layer in Examples 1 to 6 contains nickel oxide, and malonyl amidine hydrochloride is used as an interface modifier or is directly added to the perovskite active layer, which can reduce the direct contact between the perovskite and the nickel oxide in the hole transport layer due to incomplete coverage of the self-assembled monomolecule, thereby blocking the adverse reaction between high-valent nickel and perovskite and effectively passivating the buried interface defects.
[0149] Therefore, the perovskite solar cells of Examples 1 to 7 all achieved good performance. From the test results in Table 1, it can be seen that the photoelectric conversion efficiencies were 23.39%, 21.35%, 22.18%, 22.67%, 22.29%, 22.54%, 22.16%, and 22.93%, respectively.
[0150] In Comparative Example 1, malonyl amidine hydrochloride was not used as an interface modifier to prepare the interface modification layer, nor was it added to the perovskite precursor solution to prepare the perovskite active layer. The photoelectric conversion efficiency of the prepared perovskite solar cell was only 20.33%.
[0151] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A perovskite solar cell, characterized in that: The method for preparing the perovskite solar cell includes method one, method two or method three. The method 1 comprises the following steps: dissolving malonyl amidine hydrochloride in a solvent to obtain a malonyl amidine hydrochloride solution, coating the malonyl amidine hydrochloride solution on the surface of a hole transport layer to form an interface modification layer, and then preparing a perovskite active layer on the surface of the interface modification layer; The second method comprises the following steps: Adding malonyl amidine hydrochloride to a perovskite precursor solution, and coating the perovskite precursor solution with the malonyl amidine hydrochloride added on the surface of the hole transport layer to prepare a perovskite active layer; The method three comprises the following steps: Malonyl amidine hydrochloride is dissolved in a solvent to obtain a malonyl amidine hydrochloride solution, the malonyl amidine hydrochloride solution is coated on the surface of the perovskite active layer to form an interface modification layer, and then a hole transport layer is prepared on the surface of the interface modification layer.
2. The perovskite solar cell according to claim 1, characterized in that In the method 1, the mass concentration of malonyl amidine hydrochloride in the malonyl amidine hydrochloride solution is 0.1 mg / mL to 3 mg / mL; And / or, the solvent includes at least one of isopropanol and ethanol.
3. The perovskite solar cell according to claim 1, characterized in that In the method 1, the interface modification layer is prepared by spin coating; And / or, after the malonyl amidine hydrochloride solution is coated on the surface of the hole transport layer, an annealing treatment is further performed.
4. The perovskite solar cell according to claim 3, characterized in that: The interface modification layer is prepared by spin coating, the spin coating rotation speed is 3000 rpm to 4000 rpm; and / or the spin coating time is 30s to 35s.
5. The perovskite solar cell according to claim 3, characterized in that: After the malonyl amidine hydrochloride solution is coated on the surface of the hole transport layer, an annealing treatment is further performed, and the annealing temperature is 100° C. to 150° C.; and / or the annealing time is 10 min to 30 min.
6. The perovskite solar cell according to claim 1, characterized in that: In the second method, the mass concentration of malonyl amidine hydrochloride in the perovskite precursor solution is 0.1 mg / mL to 3 mg / mL.
7. The perovskite solar cell according to claim 1, characterized in that: In the method three, the mass concentration of malonyl amidine hydrochloride in the malonyl amidine hydrochloride solution is 0.1 mg / mL to 3 mg / mL; and / or the solvent includes at least one of isopropanol and ethanol.
8. The perovskite solar cell according to claim 1, characterized in that: In the method 1, the perovskite solar cell includes, from bottom to top, a transparent conductive oxide layer, a hole transport layer, an interface modification layer, a perovskite active layer, an electron transport layer, a hole blocking layer and a back electrode.
9. The perovskite solar cell according to claim 1, characterized in that: In the second method, the perovskite solar cell includes, from bottom to top, a transparent conductive oxide layer, a hole transport layer, a perovskite active layer, an electron transport layer, a hole blocking layer and a back electrode.
10. The perovskite solar cell according to claim 1, characterized in that: In the method three, the perovskite solar cell includes, from bottom to top, a transparent conductive oxide layer, an electron transport layer, the perovskite active layer, the interface modification layer, the hole transport layer and a back electrode.